T-Cell Phenotype and Function following a First cART Regimen Containing Either a Protease Inhibitor or a Non-Nucleoside Reverse Transcriptase Inhibitor in HIV-Infected Late Presenters: Results from a Retrospective, ex vivo Study. Issue 2 (February 2016) - Tincati, Camilla; Savoldi, Alessia; Cannizzo, E Stefania; Bellistrì, Giusi M; Termini, Roberta; Garau, Marzia; Mancusi, Daniela; Monforte, Antonella d'Arminio; Marchetti, Giulia
Background: We aimed to comparatively assess darunavir/ ritonavir (DRV/r) and efavirenz (EFV)-based first-line cART regimens in the reconstitution of T-cell phenotype and function in HIV-infected, late presenter subjects. Methods: Retrospective, ex vivo study on stored peripheral blood mononuclear cell samples of cART-naive, HIV-infected individuals with CD4 + T-cell counts <50>250/μl upon cART initiation with either DRV/r or EFV as third drugs of standard antiretroviral regimens. CD4 + and CD8 + T-cell maturation (CCR7/CD45RA) and proliferation (Ki67), CD8 + T-cell activation (CD38/HLA-DR) as well as HIV- and cytomegalovirus (CMV)-specific responses (CD4/CD8/IL-2/IFN-γ) were studied by flow cytometry at baseline (T0), T3, T6 and T12 months. Soluble inflammatory markers (IL-6 and sCD14) were measured in plasma at T0 and T12. Wilcoxon and Mann–Whitney tests were used for statistics. Results: A total of 19 patients started DRV/r and 15 EFV. Both regimens accounted for suppression of the HIV RNA load (<40 copies/ml), reconstitution of absolute CD4 + T-cells and CD4 + /CD8 + T-cell ratio. All study participants displayed a significant decrease of activated HLA-DR + CD38 + CD8 + T-cells at all study time points, yet no differences were found between study groups in T-cell activation and maturation phenotype. From a functional standpoint, only individuals receiving DRV/r displayed transitory recovery of HIV-specific IL-2 + IFN-γ - CD4 + T-cells (T3: P =0.006) and IL-2 - IFN-γ + CD8 + T-cells (T3: P =0.032). Conclusions: DRV/r- and EFV-based regimens have an equal effect on T-cell phenotype and function in HIV late presenters. A temporary restoration of HIV-specific T-cell immunity early in the course of therapy with DRV/r possibly implies a more effective control over HIV in the first months following a PI/r-based regimen, even at late stage of disease.